PERAN HUKUM ASURANSI DALAM PENGIRIMAN BARANG OLEH PERUSAHAAN EKSPEDISI - Halomoan, Yosua Alexander; T. Vaison Siahaan; Mangisi Simanjuntak (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The business activities of shipping goods carried out by shipping companies have increased today, with the increasing number and development of shipping companies, the possibilities of risks that will arise in shipping are also developing. These risks include loss, damage, destruction due to errors/omissions in delivery or due to other errors caused by natural factors. In discussing the problems above, the author uses normative legal research methods, using secondary data in the form of legal materials consisting of primary, secondary, and tertiary legal materials. Where the author describes the legal role of insurance in the delivery of goods carried out by the expedition in accordance with applicable regulations. Based on the results of the author’s research and analysis, legal protection for shippers already exists and is regulated in the KUHD, Civil Code, and applicable laws, but the implementation regulations to protect the shipper during the delivery process do not regulate the amount of compensation in accordance with the value of the goods purchased. sent so that many use insurance services as a risk transfer agency. For its application in insurance law, the insured party often experiences obstacles in the process of claiming compensation. So that the insured party must also take various legal efforts to obtain compensation from the insurer.